Human rights enforcement and implementation mechanisms a practical guide to the United Nations and the Organisation of African Unity human rights protection mechanisms - Matsheza, Philliat; Zulu, Leonard (Human Rights Trust of Southern Africa, 2001)
This guide explains the main human rights mechanisms of the United Nations and the Organisation of African Unity. The guide introduces the reader and user to a functional understanding of the often complicated procedures associated with human rights implementation and enforcement mechanisms available at the international level.